Action Confidence as an Indicator of Transformative Change. (January 2021) - Pomeroy, Eva; Oliver, Keira
This article reports on the findings from an interview-based, qualitative study of adult learners in Scotland participating in the MITx u.lab massive open online course in 2015 and 2016. It focuses on interviewees' accounts of the impact of participating in u.lab on their work and lives. Using grounded theory as an analytical guide, we explore participants' perceptions of the impact of their engagement in the learning process, which reflects intrapersonal, relational, and systemic learning. Through these accounts, we became particularly interested in participants' relationship to taking action and the way this changed over the course of their participation in the learning process. We conclude that an embodied change in one's perception of the nature and purpose of action—something we call "action confidence"—is reflective of transformative learning as it indicates a significant epistemological change for participants.